Quantitative NS1 antigen and the severity of dengue virus infections - Ni Made Adi Purnami; Mohammad Juffrie; Made Gde Dwi Lingga Utama (Indonesian Pediatric Society Publishing House, 2015)
Background Dengue infection is one of the main cause of morbidity and mortality in children in Indonesia. Since it is known that earlier treatment and supportive therapies can decreased case fatality rate from dengue hemorrhagic fever (DHF), identification of children who have risks to develop to DHF must be quickly identified, mainly in areas of endemic. Objective To find a correlation between increased quantitative secreted nonstructural protein-1 (sNS1) with clinical course of severe dengue infections. Methods This was a cross-sectional study conducted on children with dengue infections in Tropical Infections Division of Child Health Department, Sanglah Hospital, Denpasar. Detection of the dengue antigen was made by examining sNS1 quantitative immuno-assay. Analysis correlation of Spearman test was used to look the relationship between increased quantitative sNS1 with clinical course of severe dengue infections. Results There was a positive relationship between quantitative sNS1 and clinical course of severe dengue infections with a value of r = 0.903, P=0.001. Increased sNS1 level had a positive correlation with more severe dengue infections. Conclusions Quantitative sNS1 titer has a strong positive correlation with clinical course of severe dengue infections.